2017
DOI: 10.1558/cam.30587
|View full text |Cite
|
Sign up to set email alerts
|

Cardiologists’ experiences and perceptions of patient involvement and communication related to shared decision-making regarding atrial fibrillation treatment

Abstract: One key to improving compliance with legislation aimed at increasing patient involvement in treatment decisions could lie in paying attention to physician-patient communication and the conditions for patient involvement in decision-making about treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The purpose of the law is to create a better balance of patientempowerment between patients and staff, thereby enhancing patients' influence over their own health care. Published studies on patient involvement have also shown that patient involvement in their health care is a high priority, and patients' lack of determination and autonomy lead to major challenges (Elwyn & Miron-Shatz, 2010; Ij€ as-Kallio, Ruusuvuori, & Per€ akyl€ a, 2010; Siouta, Hellstr€ om Muhli, Fossum, & Karlgren, 2017). This study concerning the topic of the discharge process is relevant in today's fast pace turnover of hospital patients where patient involvement is becoming more and more central to the health policy and practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of the law is to create a better balance of patientempowerment between patients and staff, thereby enhancing patients' influence over their own health care. Published studies on patient involvement have also shown that patient involvement in their health care is a high priority, and patients' lack of determination and autonomy lead to major challenges (Elwyn & Miron-Shatz, 2010; Ij€ as-Kallio, Ruusuvuori, & Per€ akyl€ a, 2010; Siouta, Hellstr€ om Muhli, Fossum, & Karlgren, 2017). This study concerning the topic of the discharge process is relevant in today's fast pace turnover of hospital patients where patient involvement is becoming more and more central to the health policy and practice.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with the Swedish health-care system, health-care providers are obliged by law to ensure that the patient has understood the information given at hospital discharge by having a dialogue with the patient (Swedish Code of Statutes, 2017). However, many studies have shown that there are shortcomings in the discharge process regarding communication with and information provided to patients (Hesselink et al, 2014;Muhli, Trost, & Siouta, 2019;Popejoy, Moylan, & Galambos, 2009;Siouta, Hellstr€ om Muhli, Fossum, & Karlgren, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This study was conducted to explore the implications of the discursive movement. According to the discourse, both the effort to improve patients’ quality of life and the endeavor to reduce society’s costs are important driving forces in this development ( Castro et al, 2016 ; EPF, 2016 ; Hewitt-Taylor, 2015 ; Schofield et al, 2012 ; Siouta, 2016 ; Siouta et al, 2019 ; Slater, 2006 ; WHO, 2016 ). The goal is that the patient should be active and involved in all aspects of his or her own care ( Ekman et al, 2011 ; Hewitt-Taylor, 2015 ; Siouta, 2016 ; Siouta et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the discourse, both the effort to improve patients’ quality of life and the endeavor to reduce society’s costs are important driving forces in this development ( Castro et al, 2016 ; EPF, 2016 ; Hewitt-Taylor, 2015 ; Schofield et al, 2012 ; Siouta, 2016 ; Siouta et al, 2019 ; Slater, 2006 ; WHO, 2016 ). The goal is that the patient should be active and involved in all aspects of his or her own care ( Ekman et al, 2011 ; Hewitt-Taylor, 2015 ; Siouta, 2016 ; Siouta et al, 2019 ). This endeavor, in terms of patient centering, has influenced national guidelines and policy in various countries and organizations including the US, the UK, Australia, New Zealand, Norway, and Sweden, as well as the EU and World Health Organization (WHO) ( Broom et al, 2019 ; Hewitt-Taylor, 2015 ; Kitson et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation